2001
DOI: 10.1248/cpb.49.118
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronate Depolymerization Following Thermal Decomposition of Oxytetracycline.

Abstract: Hyaluronate (HA) is a glycosaminoglycan ubiquitously distributed in organisms. It has a linear structure without side chains, and a molecular weight of 10 4 to 10 7 . The huge molecular mass characterizes the physiologic and physicochemical properties of HA. High-molecular-weight HA forms entangled networks, having unique viscoelasticity and waterholding ability.1) The characteristics are molecular-weightsensitive, and yet, high molecular weight HA is easily depolymerized by various physical and chemical facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…5 shows the partial depolymerisation related to the initial Mw. Under our incubation conditions, the OTC-HA ratio was equivalent (250 l HA and 250 l OTC at three different concentrations), meaning that the interaction of OTC with HA was lower than in the experiments of Miyazaky et al [8], where tetracycline solutions were mixed with HA at final concentration of 0.1%. These authors obtained high levels of depolymerisation (over 70%) after 10 h of incubation at 37 • C with 4 mM OTC.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…5 shows the partial depolymerisation related to the initial Mw. Under our incubation conditions, the OTC-HA ratio was equivalent (250 l HA and 250 l OTC at three different concentrations), meaning that the interaction of OTC with HA was lower than in the experiments of Miyazaky et al [8], where tetracycline solutions were mixed with HA at final concentration of 0.1%. These authors obtained high levels of depolymerisation (over 70%) after 10 h of incubation at 37 • C with 4 mM OTC.…”
Section: Resultsmentioning
confidence: 63%
“…doi:10.1016/j.ijbiomac.2004.12.003 molecular weight HA is readily depolymerised by several different physical and chemical factors. There are many reports about HA depolymerisation by photo, thermal, mechanical and chemical actions [8]. Miyazaki et al [9] reported HA depolymerisation by phenothiazines and sulfacetamide with UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Tetracyclines are photosensitive and release ROS when exposed to light or heat, which is a frequent cause of phototoxicity induced by these antibiotics. Incubation of HA at 37°C with a solution of oxytetracycline resulted in the gradual depolymerization of HA . The addition of mannitol to the solution did not inhibit the decomposition of oxytetracycline but did protect HA from damage.…”
Section: Use Of Mannitol To Inhibit Hyaluronic Acid Degradationmentioning
confidence: 95%
“…Owing to its biological safety and rheological characteristics, solutions of intact or degraded forms of NaHA have versatile uses in ophthalmic surgery as a substitute for vitreous humor, in arthritis treatment using relatively high MW molecules (41 Â 10 6 ), and in wound repair and cosmetological applications with lower MW species (o1 Â 10 6 ) [2,[5][6][7][8][9]. In addition, since NaHA can absorb large amounts of water, it can be utilized as a skin moisturizer and in hydrogel formation [5][6][7][8]. Furthermore, it also aids in the spatial arrangement of tissue due to its visco-elastic properties [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, since NaHA can absorb large amounts of water, it can be utilized as a skin moisturizer and in hydrogel formation [5][6][7][8]. Furthermore, it also aids in the spatial arrangement of tissue due to its visco-elastic properties [8]. Since the biological or pharmaceutical applications of NaHA are related to the molecular size and structure in aqueous solution, raw NaHA materials need to be processed; NaHA chains can be readily converted into smaller MW species via physical or chemical methods.…”
Section: Introductionmentioning
confidence: 99%